Executive Committee Minutes 2018-10-04 - Academic Senate:::::::::
Approval of Agenda – item added: Potential charge to Academic Advising Subcommittee. Approved. Approval of Minutes of 9/20/18 – Approved. Chair Report. President Report. Provost Report. President's Response to Faculty Consultation in University Decision Making policy. Vice Chair Report. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Ex Com Rep to SEC Report. PDS letter to Deans, Department Chairs re: teaching sensitive materials. Academic Affairs request regarding the Academic Advising policy referred to SAC. Senate Agenda.